The Relationship Between Initial Handling and Breadth Neurological Damage to Stroke Patients - Nur Linawati; Teguh Sudrajat (Indonesian Journal of Multidisciplinary Science, 2023)
Stroke is a disease that has a high mortality and disability rate, stroke sufferers need fast and precise treatment, especially at the golden time where it is the best time to deal with stroke. This study aims to determine the relationship between initial treatment and the extent of neurological damage to stroke patients. The research used quantitative methods with a cross-sectional approach. Meanwhile, sampling was carried out using non-probability sampling techniques, the type of total sampling with independent variables is the initial handling of stroke at home and the dependent variable, namely neurological damage that occurs. The results showed that the initial treatment carried out at home by the family was not related to the neurological damage of stroke patients. The initial treatment of stroke was only related to the stiffness experienced by respondents. Meanwhile, the initial treatment of stroke is not related to feeling bad, visual impairment, dizziness, confusion, balance disturbance, headache, paralysis, loss of taste, impaired field of view, difficulty forming words, unable to speak, impaired perception, impaired orientation, and level of consciousness.